Regime Change and Dominant Capital: Lessons from Israel - Shimshon Bichler; Jonathan Nitzan (Capital as Power - Toward a New Cosmology of Capitalism, 2023)
Israel's ongoing crisis – or `judicial coup' in popular parlance – has elicited two opposite responses. The first comes from global rating agencies, economists and investment strategists who see Israel's country risk rising. The opposite reaction, by Prime Minister Netanyahu and his acolytes, insists that the `coup' is much ado about nothing, and that the country remains stable and strong as ever. So, who is right?
Keywords: P16; F; P26; G01; H12; F36; 330; Benjamin Netanyahu; crisis; differential accumulation; dominant capital; Israel; fascism; globalization; leaders; neoliberalism; redistribution; religion; ruling class; stock market